A sustainable protocol for the synthesis of N-acyl tryptamines, a class of potential gut microbiota-derived endocannabinoid-like mediators - Villano, Rosaria; Di Marzo, Vincenzo (Frontiers in Chemistry, 2024)
A simple and sustainable propylphosphonic anhydride (T3P)-assisted methodology for the synthesis of N-acyl tryptamines, an interesting class of gut microbiota-derived endocannabinoid-like lipid mediators, was proposed. This protocol is characterized by great operational simplicity, and all products were obtained at room temperature, without the use of an inert atmosphere and by using limited amounts of non-halogenated solvents. Finally, the possibility to realize the reaction under mechanochemical conditions was explored with interesting results.